PRAKTIK PENANGGULANGAN RISIKO BENCANA GEMPA BUMI PARTISIPATIF DI DESA WAWORAHA, KABUPATEN KONAWE - Haraty, Syamsul Razak; Rubaiyn, Al; Salihin, L. M. Iradat; Jahidin, Jahidin; Saleh, Fitra; Hidayat, Ahmad (....-...., 2023)
Disaster management practices are very important in Waworaha Village which is geographically prone to disasters. This service is in the form of assistance for participatory disaster management practices in Waworaha Village which is intended to organize and provide disaster-prone information services, especially related to the preparation of disaster risk assessments, as well as community-based disaster-prone information communication and education in the village and organize and provide disaster prevention and preparedness service activities. Based on the history of disaster events, natural disasters that occur in Waworaha Village are earthquakes. The earthquake disaster risk of Waworah Village is included in the low and medium categories. As a form of prevention and preparedness, a disaster risk reduction forum and local training activities were established. This has made Waworaha Village a disaster resilient village.